Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada Owaystore Pamulang - Siti Nurilla Wahidah; Ivantan Ivantan (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the effect of service quality and product quality on customer satisfaction at Owaystore Pamulang. This study uses a quantitative method with a survey approach. Data were obtained by distributing questionnaires to 98 respondents who were Owaystore Pamulang consumers. The sampling method used the Slovin formula theory. Analysis used regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study are that Service Quality (X1) and Product Quality (X2) have a significant effect on Consumer Satisfaction (Y) with the regression equation Y = 8.003 + 0.604 (X1) + 0.192 (X2). The coefficient of determination has a simultaneous effect of 68.442%. The partial hypothesis test obtained the result of Service Quality (X1) of t count > t table or (13.769 > 1.661) so H0 is rejected and H1 is accepted. This means that there can be a significant influence between the independent variable, namely Service Quality (X1) on Consumer Satisfaction (Y). The partial hypothesis test obtained the result of Product Quality (X2) of t count > t table or (10.406 > 1.661). Therefore, H0 is rejected and H1 is accepted. This means that there is a significant influence between the independent variable, namely Product Quality (X2), on consumer satisfaction (Y). Simultaneous hypothesis testing between the variables of Service Quality (X1) and Product Quality (X2) obtained the results of the F count test > F table or (99.013 > 3.09). Thus, H0 is rejected and H3 is accepted, meaning that Service Quality (X1) and Product Quality (X2) together have a significant influence on Consumer Satisfaction (Y). Keywords: Service Quality, Product Quality and Consumer Satisfaction